Is there a relationship between internet access and COVID-19 mortality? Evidence from Nigeria based on a spatial analysis - Richard Adeleke (Elsevier, 2023)
With over 6.5 million deaths due to COVID-19, it has become an issue of global health concern. Early findings have identified several social determinants of deaths from COVID-19. However, very few studies have been done on the relationship between internet access and COVID-19 mortality in the context of developing countries. Using geospatial methods, this study examines the relationship between internet access and COVID-19 mortality disparity in Nigeria. In contrast to the widely reported relationship in the literature that internet access lowers the risk of COVID-19 mortality, the current study finds that geographical locations with the highest internet access are the hotspots of COVID-19 mortality in Nigeria, especially some parts of southwest Nigeria. In addition, findings show that population density and unemployment are risk factors of COVID-19 mortality. The study recommends educating the population on the use of online health information and the need to adhere strictly to non-pharmaceutical and vaccination interventions to reduce the number of deaths caused by the virus.